2001
DOI: 10.1002/ijc.1286
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-dependent cell-mediated cytotoxicity can be induced by MUC1 peptide vaccination of breast cancer patients

Abstract: Key words: MUC1; breast cancer; ADCC; NK cells; vaccination; immunotherapyMUC1 is a transmembrane O-linked glycoprotein present on the apical surface of normal secretory epithelial cells. 1 The extracellular domain of MUC1 consists mainly of a variable number of tandem repeats 2 and it has a cytoplasmatic tail of 69 amino acids. 3 In the vast majority of human adenocarcinomas this protein is over-expressed and hypo-glycosylated 4 exposing an immunodominant repetitive amino acid sequence. The overproduction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 47 publications
1
49
0
1
Order By: Relevance
“…The MUC1-KLH plus QS-21 conjugate vaccine fails to induce a consistent T-cell response against MUC1 despite the fact that it does induce consistent IgM and IgG antibodies against MUC1, which were able to mediate ADCC in a pattern consistent with a T-helper cell 1 response. 44 The strong proliferation and interferon gamma ELISPOT reactivity against KLH that we demonstrate here suggest that this Thelper 1-type antibody response is a consequence of the help provided by KLH.…”
mentioning
confidence: 82%
“…The MUC1-KLH plus QS-21 conjugate vaccine fails to induce a consistent T-cell response against MUC1 despite the fact that it does induce consistent IgM and IgG antibodies against MUC1, which were able to mediate ADCC in a pattern consistent with a T-helper cell 1 response. 44 The strong proliferation and interferon gamma ELISPOT reactivity against KLH that we demonstrate here suggest that this Thelper 1-type antibody response is a consequence of the help provided by KLH.…”
mentioning
confidence: 82%
“…HuHMFG1 has been demonstrated to be a potent mediator of ADCC by recruiting natural components of the body's immune system (Snijdewint et al, 2001) HuHMFG1 binds to the extracellular MUC1 peptide sequence, PDTR. These sequences are not exposed in normal cells because of full glycosylation, but aberrant glycosylation in cancer cells exposes the epitope to the antibody.…”
mentioning
confidence: 99%
“…15) HuHMFG-1 induced strong ADCC to breast cancer cells and is currently being used in clinical studies on breast carcinoma. 16,17) Herein, we investigated the effect of antibody immunotherapy of anti-MUC1 mAb to oral squamous cell carcinomas, and demonstrated that anti-MUC1 mAb C595 was able to kill OSCC cells mediated by CDC and ADCC, and these effects were strongly correlated with MUC1 expression.…”
Section: Discussionmentioning
confidence: 99%